STRATEGI PENGEMBANGAN AGROINDUSTRI PERIKANAN LAUT DI KABUPATEN TUBAN - Fatih, Cholid (Jurnal Sosial Ekonomi Pertanian, 2010)
The objective of this reserach is to identify the model and strategy development of marine fishery agroindustry that consists of: fish drying, fish crackers, fish curing and also fishing business which are the upstream industry as an input producer for agroindustry of marine fishery. Through the Force Field Analysis the research using purposive technique (Nazir, 1999) was conducted in District of Tambakboyo, Tuban Regency. The conclusions of this research are: (1.) Development of marine fishery agroindustry is positive, where the driving factors are more dominant than the restraining factors. (2.) Activities and investments that can be done in the development of marine fishery agroindustry are cooperative network building of production equipment procurement and distribution, formation and development of agribussiness clinics, formation and development of Agribusiness Forum, formation and development of Agribusiness Clinics, formation and development of Agribusiness Sub-Terminal, repair of facilities and supporting infrastructure, and role support of goverment.Keywords: Agroindustry marine fishery, model and strategy, force field analysis